Contradictions of Online Motorcycle Taxi (Ojek) Arrangements as Public Motor Vehicles in Indonesia - Alifa Nurin Sabrina; Rizkia Aisyah Nur; Safira Oktavia Putri (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
There are various types of transportation services as facilities for community mobilization in Indonesia, one of them is an Ojek. Ojek as a two-wheeled transportation service considered as alternative public transportation which can transport a person from one place to another in a fast way and at affordable costs. With the development of technology and transportation in this digital era, conventional motorcycle taxi (in Indonesia: ojek konvensional) transformed into online motorcycle taxi (known as ojek online), a transportation service using an online application as the ordering media. However, currently, there is no regulation that regulates or legalizes the existence of the motorcycle taxi itself, until the emergence of online motorcycle taxi. With the issuance of Minister of Transportation Law Number 12 of 2019, which gave a perspective that motorbikes were legalized into public transportation, while the regulation in Indonesia Transportation Law stated that motorbikes were not public transportation and Constitutional Court Decision Number 41/PUU-XVI/2018 refuse the legality of motorbikes as the public transportation. The contradiction of the regulation of online motorcycle taxi has resulted an unclear legality of motorbikes used as an online transportation in Indonesia. Transportation Law as a higher regulation than Minister of Transportation Law does not regulate the classification of motorbikes as a public transportation which resulted a contradiction on the basis of the hierarchy of laws in Law Number 12 of 2011.